Penerapan Data Mining Untuk Mendeteksi Tingkatan Stadium Penyakit Human Immunodeficiency Virus / Acquired Immune Deficiency Syndrome (Hiv/Aids) Menggunakan Algoritma Naive Bayes Classifier (Studi Kasus Pada Rumah Sakit Umum Daerah (Rsud) Anutapura Palu) - Dodu, A. Y. Erwin; Nugraha, Deny Wiria; Ayyub, Mohammad Azhar (Fakultas Teknik, Universitas Tadulako, 2018)
At Anutapura Palu General Hospital (Hospital) Anutapura Palu to perform stadium detection still using Ms.Excel application with the result of detection is still manually input, to overcome the problem the author aims to make data mining applications to detect the stage of HIV / AIDS by applying Naive Bayes algorithm with output / output result of stadium 1, stadium 2, stadium 3 and stadium 4. The research data was obtained at Anutapura Palu General Hospital (RSU) from 305 HIV / AIDS patients. Existing data were analyzed using Naive Bayes algorithm and using 11 features. Naive Bayes aims to classify data in a particular class, then the pattern can be used to determine the level of stadium suffered by HIV / AIDS patients.